Public key searchable encryption scheme based on blockchain - Ruizhong DU; Ailun TAN; Junfeng TIAN (Tongxin xuebao)
Aiming at the trapdoor security problem of the public key encryption scheme,a random number constructing trapdoor and index was introduced to defend against keyword guessing attacks from the server and avoid data leakage caused by server curious behavior.Research on trusted issues of third parties,the blockchain mechanism with a searchable encryption scheme was combined,and smart contracts as trusted third parties for retrieval was used,which could prevent keyword guessing attacks inside the server and ensure retrieval.The correctness of the results,thereby limiting the malicious behavior of the server when sending data.The solution was analyzed for security and the verification scheme satisfies IND-KGA security.Experiments in real data sets,compared with other programs,prove that the program has certain advantages in time overhead.